2013
DOI: 10.9790/487x-1336164
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management; concepts, benefits and process

Abstract: In order to improve the companies, it is important to know what is its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We also have the intangible resources, that is, everything that is not physical, such as the company's reputation, competence, human resources, this type of resources is what allows companies to achieve sustainable competitive advantage. With these resources, the RBV also argues that they should be heterogeneous, i.e., different from company to company, increasing their diversity and immovable, preventing them from being acquired by their competitors (Sourkouhi, 2013).…”
Section: Resource Based Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…We also have the intangible resources, that is, everything that is not physical, such as the company's reputation, competence, human resources, this type of resources is what allows companies to achieve sustainable competitive advantage. With these resources, the RBV also argues that they should be heterogeneous, i.e., different from company to company, increasing their diversity and immovable, preventing them from being acquired by their competitors (Sourkouhi, 2013).…”
Section: Resource Based Viewmentioning
confidence: 99%
“…-Organized (O): What is the point of having a resource if the organization that owns it cannot use it? It is important to have resources that can be fully used (Combe, 2020;Salazar, 2017;Sourkouhi, 2013). RBV argues that sustained competitive advantage can only be achieved by exploiting internal factors, in 2012 a study was done which showed between 30-45% of organisational performance was through RBV and 20% through external effects, RBV obviously having a greater impact on business performance (Frank et al, 2012).…”
Section: Resource Based Viewmentioning
confidence: 99%
“…The resources-based theory, as argued by Sourkouhi et al (2013), states that aspiring multinational companies need to act on the assumption that a company's resources are homogeneous with a strong strategic management business position. According to this framework, a multinational company has perfect mobility of resources, otherwise trying to go multinational will be a long process.…”
Section: Firm-based Advantage Theoriesmentioning
confidence: 99%
“…Management is the science of formulating, implementing and assessment crossfunctional decisions that will enable an organization to reach its goals and objectives. Further, benefi ts and process specifying the company's goals, nurturing policies and strategies to reach these goals and obtaining and making available these resources to perform the policies and strategies to achieve the company's goals (Sourkouhi, 2013). In the religious organization, it refers to the anticipation of demand, optimization of availability and pricing, the achievement of the best possible fi nancial result and management of revenue.…”
Section: Introductionmentioning
confidence: 99%